Kepatuhan Remaja Minum Tablet Tambah Darah Sebelum dan Setelah Menggunakan Aplikasi Reminder (Pengingat) - Silvi Maya Asrina; Arika Indah Setyarini; Ratih Novitasari (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2021)
The prevalence of anemia caused by iron deficiency is still a problem for adolescent girls in Kediri Regency. Based on data at SMA 1 Mojo, it is known that there were 85 students suffering from anemia in 2019 and from 2020 to January there were 32 students. This study uses a reminder application used as a reminder of the time to take blood-added tablets. The purpose of this study was to determine the differences in the use of an Android application-based reminder to drink blood-added tablets on the compliance of anemic adolescents in SMA 1 Mojo, Kediri Regency. The research design used one group pretest-posttest. A sample of 30 students was selected by simple random sampling. The results showed that the mean of pretest compliance was 3.2 and the average posttest was 6.5. The results of the analysis using the Wilcoxon Match Pairs Test showed that there was a significant difference in adherence before and after being given a reminder application (p-value <0.001). This increase in compliance occurs because of the reminder application as a reminder to consume blood-added tablets according to the time recommended by health workers. Keywords: anemia adolescent, reminder application, compliance